2020
DOI: 10.1038/s41467-020-17593-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order quantum spin Hall effect in a photonic crystal

Abstract: The quantum spin Hall effect lays the foundation for the topologically protected manipulation of waves, but is restricted to one-dimensional-lower boundaries of systems and hence limits the diversity and integration of topological photonic devices. Recently, the conventional bulkboundary correspondence of band topology has been extended to higher-order cases that enable explorations of topological states with codimensions larger than one such as hinge and corner states. Here, we demonstrate a higher-order quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
76
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 55 publications
0
76
1
Order By: Relevance
“…Meanwhile, the experimental quest for higher-dimensional non-Hermitian systems is still absent. On another front, the rising of higher-order topological insulators (HOTIs) provides a realm where band topology delicately interplays with crystalline symmetries and leads to multidimensional topological physics [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] . At the interface between the non-Hermitian physics and HOTIs, little is known in theories or experiments.…”
mentioning
confidence: 99%
“…Meanwhile, the experimental quest for higher-dimensional non-Hermitian systems is still absent. On another front, the rising of higher-order topological insulators (HOTIs) provides a realm where band topology delicately interplays with crystalline symmetries and leads to multidimensional topological physics [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] . At the interface between the non-Hermitian physics and HOTIs, little is known in theories or experiments.…”
mentioning
confidence: 99%
“…[16][17][18] Such a behavior is the key advantage over the conventional photonic structures and make them useful for the practical applications. As novel topological phases, higher-order topological insulating (HOTI) phases have recently been discovered in various quantum and classical systems, including crystalline [19] and amorphous materials, [20,21] photonic [15,16,[22][23][24][25][26][27][28][29][30][31] and phononic The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/andp.202100075 DOI: 10.1002/andp.202100075 crystals, [32][33][34][35] and electric circuits. [36,37] As one of the most well-known and simplest second-order topological insulator (SOTI), one might take the SOTI in the systems described by 2D SSH model (see, e.g., ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new class of higher-order TPCs has been extensively investigated. [39] In contrast to the TPCs with bulk-boundary correspondence, the higher-order TPCs support topological states with dimensionality two lower than the system, thereby offering us additional degrees of freedom to manipulate light flow. [40] By now, it has been observed that second-order TPCs may support 0D corner state, which is highly localized and exhibits nonradiative characteristic.…”
Section: Introductionmentioning
confidence: 99%